Estudo de processo de retificação aplicado à recuperação de placas de molde de máquinas de lingotamento contínuo de placas de aço - Mendes, Alexandre Avelar Alves (2011)
This studypresents an alternative forrecuperation by machining of the ArcelorMittal Tubarao Continuous Casting Machine wide copper plates proposing a grinding process instead of the current ones (planning or boring). Some of the variables that motivated this study werethe leadtime required to complete the current machining operationsand because the proposed process confronts with the paradigm of the grinding applied to ductile materials.In addition to those variables in an academic and practical sense thesuperficial roughness may influence the mold thermal control and slabs superficial quality. The grinding process proposed evaluated the influence of the feed rate and cut depthin the specimens’ roughness. Based upon a broad revision of the related literature, a theoretical reference has been established to investigatethecurrentand the proposed machining operations, towards thecharacteristics and limitations analysis and comparison.In addition tothe current and proposed processesaspects, this study presents a general review ofsteel slabs continuous castingand tribological aspects related to the abrasive machining operations. The conclusion presents positive results in terms of superficial roughness and productivity if compared to conventional mold repair processes, also indicating the technical feasibilityof the grinding as a sustainable process